Prognoza migracji pracowników z krajów obecnie kandydujących do Unii Europejskiej - Krawczyk, Ewa; Albin, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2002)
The reasons for workers' migration resulting from personal features of a worker as well as from general political and economic situation both in the worker' s home country and in the host country were discussed in the paper. As regards to movement of workers between the candidate countries and the Member States, the economic factors seem to be of a key importance. They include differences in macroeconomic situation between states, income disparities and demand-supply relationship on certain labour markets. According to migration predictions presented in the study, the EU' immigration from all candidate Central and Eastern European countries should reach the level of 335 thousands of persons in the first year of accession. The outlook for year 2030 shows, that total number of immigrants from ten CEECs remaining residents in present Member States would achieve about 3.9 million of persons. It means that their percentage in the EU population would increase from 0.2 per cent at present to 1.1 per cent in 2030. Basing on the experience of earlier enlargements of the EU, the opinion polls within potential immigrants, studies, reports and forecasts worked out by research institutes, we can conclude that setting the EU labour markets free for nationals of the candidate countries would not cause the mass labour migration from CEECs.